Urban brownfields as temporary habitats: driving forces for the diversity of phytophagous insects - Strauss and Robert Biedermann, Barbara (Ecography (Copenhagen), 2006)
In urban brownfields (derelict sites), we studied the influence of local factors (successional age, vegetation structure, soil) and landscape context (spatial arrangement of brownfields of different successional stages) on the diversity of phytophagous insects, grasshoppers and leafhoppers (Orthoptera and Hemiptera: Auchenorrhyncha). The study was conducted on a total of 246 plots in the cities of Bremen and Berlin, Germany. We used a habitat modelling approach, enabling us to predict the community from single species models (30 species in Bremen, 28 in Berlin). The results revealed that communities were predominantly determined by vegetation structure, followed by landscape context, soil parameters and site age. For most species, local factors were the most important. Only few species were strongly influenced by landscape context, even though some showed clear negative reactions to low proportions of brownfields in the surroundings. Along a successional gradient of vegetation structure, from scarce and low to dense and high vegetation, the insect community was not static. Even though species numbers remained comparatively constant, species composition changed considerably. Many species showed clear preferences for certain successional stages. Thus, maintaining the regional species pool of a city requires a mosaic of all successional stages.